2012
DOI: 10.2147/ijn.s34801
|View full text |Cite
|
Sign up to set email alerts
|

A MSLN-targeted multifunctional nanoimmunoliposome for MRI and targeting therapy in pancreatic cancer

Abstract: Pancreatic cancer is a highly lethal disease with a 5-year survival rate less than 5% due to the lack of an early diagnosis method and effective therapy. To provide a novel early diagnostic method and targeted therapy for pancreatic cancer, a multifunctional nanoimmunoliposome with high loading of ultrasmall superparamagnetic iron oxides (USPIOs) and doxorubicin (DOX) was prepared by transient binding and reverse-phase evaporation method, and was conjugated with anti-mesothelin monoclonal antibody by post-inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Polydispersity index (PDI) of 0.10 suggested a very narrow size distribution range of this formulation. Encapsulation of MNPs into the liposomes was proved to be difficult task and a maximum of 15% EE had been shown earlier [36]. We here reported EE of 60.0% which could possibly be attributed to the ultrasmall sized MNPs.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Polydispersity index (PDI) of 0.10 suggested a very narrow size distribution range of this formulation. Encapsulation of MNPs into the liposomes was proved to be difficult task and a maximum of 15% EE had been shown earlier [36]. We here reported EE of 60.0% which could possibly be attributed to the ultrasmall sized MNPs.…”
Section: Resultssupporting
confidence: 70%
“…[36] 7:2:0.5 molar ratios of EPC, Cholesterol, and mPEG2000-DSPE was thoroughly mixed in chloroform and evaporated under vacuum. 1.0 mg of ultrasmall MNPs was added onto the resultant thin lipid film for rehydration.…”
Section: Materials and Experimentalmentioning
confidence: 99%
“…The results of this study showed that M-PLDU controlled advanced inhibitory effect on the growth of the cancer and distribution assay of tissue further more verified that M-PLDUs might selectively collect in the tumor xenograft. This study shows that M-PLDU not only well retains the inherent MRI capability of USPIO, but also significantly enhances the targeted delivery of USPIO and therapeutic agents in pancreatic tumor cells [70].…”
Section: Injection Of Gemcitabine Liposome (Stealth Liposomes)mentioning
confidence: 70%
“…Similar approaches have also been evaluated using nanoparticles with MR capabilities [226234]. These studies used various types of nanoparticles, which include ultrasmall superparamagnetic iron oxide (USPIO) particles, iron oxide nanoworms, liposomes and dendrimers.…”
Section: Targeted Nanoparticle Imaging Agentsmentioning
confidence: 99%
“…The therapeutic strategies have ranged from chemotherapy ( e.g. taxanes and anthracyclines) [226, 229, 230] and small interfering RNA [233] to antiangiogenic approaches using the CREKA polypeptide and vascular blockade [232], while the target sites included the folate receptor [227, 229], urokinase plasminogen activator receptor [231], integrins [228, 234], prostate-specific membrane antigen [228]. In addition to MR, theranostic agents have been developed using radioisotopes for SPECT and PET imaging [235237].…”
Section: Targeted Nanoparticle Imaging Agentsmentioning
confidence: 99%